Journal of Otolaryngology - Head & Neck Surgery - Seikaly, Hadi; Wright, Erin D.
Journal of Otolaryngology-Head & Neck Surgery is an open access, peer-reviewed journal publishing on all aspects and sub-specialties of otolaryngology-head & neck surgery, including pediatric and geriatric otolaryngology, rhinology & anterior skull base surgery, otology/neurotology, facial plastic & reconstructive surgery, head & neck oncology, and maxillofacial rehabilitation, as well as a broad range of related topics. The journal welcomes submissions of original articles focusing on research and clinical practices on common and uncommon disorders and therapeutics, physicians' preferred technique and reviews of the literature. Journal of Otolaryngology - Head & Neck Surgery articles published prior to 2013 can be accessed by contacting the CSOHNS office.